Comprehensive analysis and prediction of long-term durability of factor IX activity following etranacogene dezaparvovec gene therapy in the treatment of hemophilia B. (1st February 2023) - Shah, Jinesh; Kim, Hongseok; Sivamurthy, Krupa; Monahan, Paul E.; Fries, Michael
Abstract: Objective: Congenital hemophilia B is a rare bleeding disorder caused by defects in the gene encoding factor IX (FIX) leading to coagulation deficiency. Recurrent bleeds may cause chronic pain, disability, and reduced quality of life. Phase 2 b and 3 single-arm, open-label, single-dose trials assessing etranacogene dezaparvovec gene therapy for hemophilia B have demonstrated sustained FIX activity levels over observed periods, but long-term durability of the treatment effect has not been established. Using statistical modeling, we estimate long-term durability of FIX activity levels after receiving etranacogene dezaparvovec. Methods: Participants from Phase 2 b ( N  = 3; NCT03489291) and 3 studies ( N  = 52; NCT03569891) were included. Two participants who did not respond to treatment were excluded. FIX activity was assessed by one-stage activated partial thromboplastin time assay. FIX activity levels at Month 6 post-treatment were considered baseline. Bayesian and Frequentist linear mixed models predicted FIX activity levels up to 25.5 years at an individual and population level with pre-treatment adeno-associated virus 5 (AAV5) neutralizing antibody (NAb) status as primary covariate. Results: Bayesian and Frequentist linear mixed models predicted no more than 6/55 (10.91%) observed participants would have FIX activity levels <2% up to 25.5 years post-infusion. Bayesian model-based predictions of future participants suggest >80% would be free from prophylactic FIX replacement products 25.5 years post-infusion. Both models predicted FIX activity levels were not significantly influenced by pre-treatment AAV5 NAb status. Conclusions: People with hemophilia B receiving etranacogene dezaparvovec would likely achieve durable FIX activity levels and remain free of prophylactic FIX replacement products for up to 25.5 years following single administration. The long-term factor IX durability predictions are based on statistical methods and results in vivo may differ. PLAIN LANGUAGE SUMMARY: Hemophilia B is a rare bleeding condition where blood does not clot properly, causing excessive bleeding. It is caused by a change or mutation to a gene, leading to lower-than-normal levels of a clotting factor, called factor IX. Standard treatment involves replacing missing factor IX through lifelong, regular treatment with factor replacement products. Etranacogene dezaparvovec is a gene therapy developed to replace the faulty gene and increase factor IX activity levels in the blood, thereby reducing bleeding, after one treatment. In clinical trials of etranacogene dezaparvovec, people with severe or moderately severe hemophilia B had stable and long-lasting increases in factor IX activity levels that reached near to the normal range seen in people without hemophilia B. The purpose of this study was to predict whether these increases in factor IX activity levels will last over an extended period of time after receiving etranacogene dezaparvovec. Mathematical predictions showed less than 11% of clinical trial participants would have unacceptable factor IX activity levels (less than 2%) up to 25.5 years after receiving etranacogene dezaparvovec. Further predictions of potential future people with hemophilia B showed that over 80% would not need treatment with factor replacement products 25.5 years after receiving etranacogene dezaparvovec. The goal of treatment is to increase factor IX activity levels into the near-to-normal range in people with hemophilia B and therefore decrease or eliminate bleeding. These results suggest people with hemophilia B receiving etranacogene dezaparvovec would have long-lasting factor IX activity levels and would not need regular factor replacement products for up to 25.5 years following a single treatment of etranacogene dezaparvovec.